2006
DOI: 10.1103/physrevlett.96.066103
|View full text |Cite
|
Sign up to set email alerts
|

Critical Adsorption of Polyelectrolytes onto Charged Spherical Colloids

Abstract: The adsorption of a flexible polyelectrolyte in a salt solution onto an oppositely charged spherical surface is investigated. An analytical solution is derived, which is valid for any sphere radius and consistently recovers the result of a planar surface in the limit of large sphere radii, by substituting the Debye-Hückel potential via the Hulthén potential. Expressions for critical quantities such as the critical radius and the critical surface charge density are provide. A comparison of our theoretical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 28 publications
7
79
1
Order By: Relevance
“…This is confirmed in ref. 13, by the agreement between the critical PE-sphere adsorption radius obtained from simulations and predicted by theory. However, for PE chains strongly adsorbed on surfaces, far from the adsorption-desorption transition, the self-interactions within the PE chain as well as the counterion release accompanied by a corresponding entropy gain, are likely to contribute significantly to the adsorption properties.…”
Section: Possible Extensions and Perspectivesmentioning
confidence: 65%
See 2 more Smart Citations
“…This is confirmed in ref. 13, by the agreement between the critical PE-sphere adsorption radius obtained from simulations and predicted by theory. However, for PE chains strongly adsorbed on surfaces, far from the adsorption-desorption transition, the self-interactions within the PE chain as well as the counterion release accompanied by a corresponding entropy gain, are likely to contribute significantly to the adsorption properties.…”
Section: Possible Extensions and Perspectivesmentioning
confidence: 65%
“…For PE-sphere adsorption, in contrast, its outcomes disagree with the scaling predictions from the WKB model presented above as well as from the approximate solution of PE-sphere adsorption problem in the Hulthen potential derived in ref. 13. Namely, in the limit of small ka, Muthukumar's model predicts a d c p (ka) 2 dependence, both for the rod and sphere situations.…”
Section: B Comparison With Other Theories and Experimental Datamentioning
confidence: 96%
See 1 more Smart Citation
“…For instance a nucleosome can be seen as an electrostatic binding between DNA and histone proteins, where the latter can be envisioned as charged spheres. ‡ Many theoreticians [95,96,97,98,99,100,101,102,92,103,104,105] have investigated these types of objects to understand the electrostatics governing those structures. Two very relevant results are: (i) the possible overcharging of the sphere by the long PE and (ii) a strong wrapping of the PE about the sphere (see figure 7 for an example).…”
Section: Oppositely Charged Spherical Substratesmentioning
confidence: 99%
“…Recent analytical studies [35,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and numerical simulations [12,13,36,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] have provided very useful insight into the essential role that electrostatic interactions play in determining the structural properties of charged polymer-sphere complexes. It was shown that a minimal chain-sphere model for nucleosome core particles [37][38][39][40][41]51] can closely predict the experimentally observed [79][80][81][82][83][84]…”
Section: Introductionmentioning
confidence: 99%